Monitoring of marketing strategies for educational services - Klimov, M. V. (WSEH, 2025)
Monitoring marketing strategies in the field of educational services is a critical component of institutional development and competitiveness. It involves the systematic evaluation of promotional activities, communication channels, and market positioning to ensure alignment with student needs and stakeholder expectations. Through continuous analysis of effectiveness, institutions can identify strengths, address weaknesses, and adapt to dynamic educational markets. Monitoring also supports evidence-based decision-making, enhances transparency, and contributes to sustainable growth by integrating feedback mechanisms and performance indicators into strategic planning.
Keywords: monitoring; marketing strategies; educational services; competitiveness; communication channels; market positioning; performance indicators; sustainable growth